Prevalence and Nature of Child Neglect and Mental Health Status of Secondary School Adolescents - Bede, Akpunne (Advances in Social Sciences Research Journal, 2015)
Child neglect results in some forms of physical, and mental illness. Research on child neglect and mental health status of Nigerian secondary school adolescents is scanty. A purposive sample of 280 senior secondary school adolescents from two Local Government Areas of Ogun State responded to Neglect Scale (NS) (Form A20) and General Health Questionnaire (GHQ-12). Both descriptive and inferential statistics were employed in the data analysis. The prevalence rate of child neglect among the adolescents ranges from 49.5% (total child neglect) to 74.2% (physical neglect). The prevalence rate of poor mental health was 35.4%.There was no significant sex difference in both child neglect and mental health status of the adolescents. Significant positive correlation was observed between child neglect and poor mental health status. Parental occupation and family size significantly influenced both child neglect and mental health status of adolescents. There was a high prevalence of child neglect and poor mental health among the adolescents. Family size and parental occupations were significant determinants of poor mental health. Secondary school curriculum should include acceptable practices in parenthood, policies on child neglect should be effectively enforced, and more research efforts on child neglect should be carried out.